INVITRO ANTIMICROBIAL ACTIVITY AND PRELIMINARY PHYTOCHEMICAL SCREENING OF METHANOL, CHLOROFORM AND HOT WATER EXTRACTS OF GINGER (ZINGIBER OFFICINALE) - BASHIR, SALIM FARUK; Gurumayum, Sushma; KAUR, SAWINDER (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim of the study was to perform in-vitro antimicrobial activity test and preliminary phytochemical screening of methanol, chloroform and hot water extract of ginger (Zingiber officinale) against microbial isolates obtained from air, sewage, and soil samples. Methods: The ginger rhizome was shade-dried and powdered using pestle and mortar. Extraction was done using methanol, chloroform, and hot water. The ginger extracts were evaluated for the presence of alkaloids, steroids, tannins, flavonoids, reducing sugars, and saponin. Preliminary antimicrobial activity of extracts was studied using agar well diffusion method on test organisms Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Aspergillus niger, Aspergillus terreus, Trichoderma viride, Fusarium oxysporum, Saccharomyces cerevisiae, and Rhodotorula sp. Evaluation of minimum inhibitory concentration against test bacterial strains was carried out. Results: Qualitative screening for presence of phytochemicals viz., alkaloids, saponin, flavonoids, steroids, tannins, and reducing sugar showed the presence of all of the above phytochemicals in methanolic extract with exception of saponin while only flavonoids and steroids were present in chloroform extract. In hot water extract, with the exception of alkaloids and flavonoids all were present. Test organisms were most susceptible to methanolic extract and showed poor susceptibility to hot water extract of ginger. The present study reveals that the pattern of inhibition varied with the solvent used for extraction and the organism tested. Gram-positive bacteria were found to be more sensitive as compared to Gram-negative bacteria, and Rhodotorula sp. was the most sensitive among fungal test strains. Fungi also showed growth retardation, discoloration and lack of sporulation on exposure to chloroform and methanolic ginger extract, but they were not affected by aqueous extract. Conclusion: The results of the study suggest that ginger extract contains bioactive compounds with antimicrobial activities. Further isolation and characterization of the bioactive components and evaluation of their individual effect as well as in combination on various test organisms may be done. Keywords: Zingiber officinale, Phytochemicals, Antimicrobial activity, Minimum inhibitory concentration, Fourier transform infrared spectroscopy. Â 